2019
DOI: 10.1016/j.cemconres.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Properties of early-age concrete relevant to cracking in massive concrete

Abstract: This paper provides an overview of the early-age properties of concrete, from a materials science and concrete engineering perspective. The aim of this manuscript is to contribute to gap analysis and to improve the strategy for evaluation methods of the risk of cracking in mass concrete. Strength, elastic modulus, and volumetric stability at early ages are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(37 citation statements)
references
References 170 publications
2
25
0
1
Order By: Relevance
“…In that context, the shrinkage can be computed once the thermal deformation is removed from the specimens’ deformation. To do so, the coefficient of thermal expansion (CTE), which varies at early age [ 36 , 37 , 38 ], must be defined.…”
Section: Resultsmentioning
confidence: 99%
“…In that context, the shrinkage can be computed once the thermal deformation is removed from the specimens’ deformation. To do so, the coefficient of thermal expansion (CTE), which varies at early age [ 36 , 37 , 38 ], must be defined.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, constant of thermic growth is a least situation and now rise by waterlessness. Figure 6 shows the formal shape for the fracturing of mass concrete (Maruyama and Lura, 2019;Zhang et al, 2015;2017). Figure 7 shows Aggregate's influence in concrete (Metha and Monteiro, 2006).…”
Section: Mixing Percentagementioning
confidence: 99%
“…Furthermore, the modelling of temperature related cracking in massive structures is known to be strongly dependent on a precise maturity model [4,9,10] that covers the full range of temperatures to be expected inside a massive concrete structure. From the observations in the present test series it is concluded that further research is needed on the temperature effects on the later-age strengths and the cross-over effect.…”
Section: Supplementary Testsmentioning
confidence: 99%